2020
DOI: 10.3390/ani10091505
|View full text |Cite
|
Sign up to set email alerts
|

Oral Transmucosal Cannabidiol Oil Formulation as Part of a Multimodal Analgesic Regimen: Effects on Pain Relief and Quality of Life Improvement in Dogs Affected by Spontaneous Osteoarthritis

Abstract: The aim of this study was to evaluate the efficacy of oral transmucosal (OTM) cannabidiol (CBD), in addition to a multimodal pharmacological treatment for chronic osteoarthritis-related pain in dogs. Twenty-one dogs were randomly divided into two groups: in group CBD (n = 9), OTM CBD (2 mg kg−1 every 12 h) was included in the therapeutic protocol (anti-inflammatory drug, gabapentin, amitriptyline), while in group C (n = 12), CBD was not administered. Dogs were evaluated by owners based on the Canine Brief Pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
129
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(138 citation statements)
references
References 49 publications
2
129
2
5
Order By: Relevance
“…There are no published studies on the efficacy of cannabinoids in cats. In dogs with osteoarthritis, CBD has been shown to reduce pain and increase mobility when administered at 1.2 mg/kg daily for 4 weeks, 3 and to reduce pain and improve quality of life when administered at 2 mg/kg q24h for 12 weeks 4 or q12h (1:1 CBD:CBDA) for 4 weeks. 5 CBD (2.5 mg/kg q12h for 12 weeks) has also been shown to decrease seizure frequency in dogs with intractable idiopathic epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…There are no published studies on the efficacy of cannabinoids in cats. In dogs with osteoarthritis, CBD has been shown to reduce pain and increase mobility when administered at 1.2 mg/kg daily for 4 weeks, 3 and to reduce pain and improve quality of life when administered at 2 mg/kg q24h for 12 weeks 4 or q12h (1:1 CBD:CBDA) for 4 weeks. 5 CBD (2.5 mg/kg q12h for 12 weeks) has also been shown to decrease seizure frequency in dogs with intractable idiopathic epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable interest in the use of CBD for both humans and companion animals due to its reported benefits, such as analgesia, anti-inflammatory, anxiolytic, and sedative effects ( 28 30 ). The analgesic effect of CBD has been documented in rodent and human models ( 31 33 ), and the use of oral and transmucosal CBD oil formulations increased the Canine Brief Pain Inventory (CBPI) and Hudson scores in dogs with osteoarthritis, suggesting an increase in activity and comfort with CBD use ( 34 , 35 ). However, despite evidence of an anxiolytic effect of CBD in both rodents and humans with doses ranging from 2.5 to 10 mg/kg ( 36 38 ), a recent report failed to demonstrate an anxiolytic effect of treats containing 1.4 mg CBD/kg body weight (BW) in dogs exposed to a noise-induced fear response test ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pain Severity Score (PSS), Pain Interference Score (PIS), and Quality of Life Index (QoL), in comparison with dogs that did not receive CBD (Brioschi et al, 2020). When considering individual results, treatment success (reduction of >1 in PSS and >2 in PIS) was obtained in more dogs in the CBD group compared with the comparator group (Brioschi et al, 2020). Verrico et al (2020) reported that owner assessment of animal symptomatology by Helsinki Chronic Pain Index (HCPI) was not significantly altered by administration of placebo or 20 mg day −1 naked CBD; however, administration of 50 mg day −1 naked CBD or 20 mg day −1 liposomal CBD generated statistically significant reductions in pain symptomatology (P < 0.01), an effect that remained statistically significant for at least 15 days after cessation of therapy (P < 0.05).…”
Section: Results With Osteoarthritismentioning
confidence: 99%